Keterampilan Belajar Mandiri Pebelajar Program Ilmu Sosial Kelas 11 Saat Pembelajaran Jarak Jauh - Nurlia, Agnes Cristin Ari; Kristin, Kristin; Lukas, Samuel; Sepsiati, Sisilia Fitri (JKTP: Jurnal Kajian Teknologi Pendidikan, 2022)
The pandemic caused changes in learning at XYZ school. The schools set synchronous and asynchronous methods to train students’ self regulation in learning. However, there were still students who experienced obstacles in terms of self regulation. It became the background of this research to measure the self regulation of 11th grade students at XYZ school. This study aimed to produce a good measuring instrument for evaluating students’ self regulation skills, knowing students’ self regulation level, and finding if there any relation between students’ gender and their self regulation among 11th grade high school students in social science programs during online learning. This study used quantitative methods with data collection techniques using a closed questionnaire using a Likert scale. The data from the questionnaire were tested for validity, reliability, and normality data. Furthermore, hypothesis testing was using mean test and chi square correlation test. The results of this study found that the measuring instrument in the form of a questionnaire with 12 statement items were all valid and reliable. The level of students’ self regulation skills was in the medium to high category and there was a relationship between student’s gender and their self regulation. Initiatives, strategies, and learning evaluation had a positive impact on students' self regulation skills.AbstrakPandemi menyebabkan perubahan dalam pembelajaran di sekolah XYZ. Sekolah menetapkan metode sinkronus dan asinkronus untuk melatih kemandirian peserta didik. Namun demikian masih ditemukan peserta didik yang mengalami kendala dalam hal kemandirian belajar. Hal ini yang melatarbelakangi penelitian untuk mengukur kemandirian belajar peserta didik kelas 11 sekolah XYZ. Penelitian ini bertujuan untuk menghasilkan alat ukur yang baik untuk mengukur keterampilan kemandirian belajar, mengetahui tingkat keterampilan kemandirian belajar, serta mengetahui apakah adanya hubungan antara gender dan kemandirian belajar peserta didik kelas 11 program ilmu sosial di sekolah XYZ dalam pembelajaran jarak jauh. Penelitian ini menggunakan metode kuantitatif dengan teknik pengumpulan data menggunakan kuesioner pertanyaan tertutup menggunakan skala Likert. Data hasil kuesioner diuji validitas, reliabilitas, dan normalitas data. Selanjutnya, pengujian hipotesis menggunakan uji mean, uji korelasi chi square. Hasil dari penelitian ini ditemukan bahwa alat ukur berupa instrumen dalam bentuk kuesioner dengan 12 item pernyataan semua valid dan reliabel. Tingkat keterampilan kemandirian belajar peserta didik masuk kategori sedang dan terdapat hubungan antara gender dengan keterampilan kemandiri belajar peserta didik. Inisiatif, strategi, dan evaluasi belajar berpengaruh positif terhadap keterampilan kemandirian belajar peserta didik.